Peningkatan Literasi Keuangan Mitra Melalui Pelatihan Pencatatan Digital Berbasis Website Akuntansi - June, Cindy Getah Trisna; Santi, Fitriana; Dalulia, Primahasmi; Agesia, Sheina Vella; Fatin, Yustinus Ricky (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
The training activity on the use of an accounting website for financial management conducted for UMKM (Micro, Small, and Medium Enterprises) “Bu Gan” in Tanjungrejo Sub-district, Sukun District, Malang City shows that business owners have been able to manage their finances independently. However, financial management issues persist, particularly the difficulty in separating personal and business needs. This prolonged problem leads to challenges in evaluating business performance, causing stagnation in business growth. To address this issue, the community service team provided a solution in the form of training on the use of an accounting website, which is expected to help business owners record every income and expense. The website also generates financial reports to assist in understanding business performance. In addition, the team conducted monitoring activities to identify obstacles faced in independent financial management.